2013
DOI: 10.1089/dna.2013.2109
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs11652075 in the CARD14 Gene as a Risk Factor for Psoriasis (PSORS2) in a Spanish Cohort

Abstract: A recent genomic survey identified the association between a common single nucleotide polymorphism (SNP) at the CARD14 gene (SNP rs11652075; p.Arg820Trp) and psoriasis (Psor). Our aim was to replicate the association between this polymorphism and to determine whether other CARD14 variants could explain the association. A total of 400 Psor patients (mean age 47±15; 55% male) and 420 healthy controls (mean age 51±16; 56% male) all Caucasian were genotyped for rs11652075. The rs11652075 CC genotype was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 19 publications
0
31
1
Order By: Relevance
“…However, some investigations with small sample sizes have obtained contrasting results (González-Lara et al, 2013;Qin et al, 2014). Functional studies of this SNP have not provided further verification.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…However, some investigations with small sample sizes have obtained contrasting results (González-Lara et al, 2013;Qin et al, 2014). Functional studies of this SNP have not provided further verification.…”
Section: Discussionmentioning
confidence: 94%
“…After selection and data extraction according to our inclusion criteria, five studies were included in our analysis, comprising 32,807 cases and 45,458 controls (Jordan et al, 2012;Tsoi et al, 2012;González-Lara et al, 2013;Qin et al, 2014;Tang et al, 2014; Table 1). Data from each subgroup were treated as independent.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, several studies have reported associations of CARD14 variants with psoriasis vulgaris, psoriatic arthritis, generalized pustular psoriasis, and palmoplantar pustular psoriasis (Ammar et al, 2013(Ammar et al, , 2016Eskin-Schwartz et al, 2016;Feng et al, 2016;Gonzalez-Lara et al, 2013;Inoue et al, 2016;Korber et al, 2013;Mossner et al, 2015;Qin et al, 2014;Sugiura et al, 2014Sugiura et al, , 2015Zhu et al, 2016). Furthermore, CARD14 variants have also been associated with pityriasis rubra pilaris, a distinct inflammatory skin disease characterized by keratotic follicular papules and salmon-colored erythematous plaques (Eytan et al, 2014;Fuchs-Telem et al, 2012;Has et al, 2016;Inoue et al, 2016;Li et al, 2015).…”
Section: Card14 Variants In Psoriasismentioning
confidence: 99%